HISTO-TOPOGRAPHICAL AND MORPHOMETRIC FEATURES’ OF GLANDS’ OF MUCOSA OF FRONT AND BACK WALLS’ OF FRONTAL SINUS OF HUMAN ARE IN A NORME - Serbin, S.I. (World of Medicine and Biology, 2012)
In work the morphometric and histo-topographical features of glands of mucosa are in-process studied by front and back walls of frontal sinus of human in a norm. It is set that their structural organization has the difficult ramified structure with eventual departments and system of deferent channels in the composition. It is set at morphometric research of external diameter of eventual departments of glands of mucosa of front wall of frontal sinus of human, that mean values made 29,85±3,04 micrometre on the left and 29,84±2,47 micrometre on the right. Meaningful differences with corresponding indexes it is not educed for a back wall, they made according to 29,77±2,07 micrometre and 30,17±2,25 micrometre.